PEMROGRAMAN PEWARNAAN GRAF PADA PENJADWALAN MATA KULIAH JURUSAN MATEMATIKA - Susila Bahri; Ghazy Muhari Novrial; Narwen Narwen (LPPM Universitas Bina Bangsa, 2023)
The scheduling of odd semester courses for the 2022/2023 Academic Year in the Mathematics and Data Science Department which is intended to avoid conflicts in the lecture implementation process, is prepared by colored dots on the graph. The dots are assumed to be courses while the edges of the graph are given to indicate that two courses cannot be arranged on the same schedule. Coloring with the Welsh-Powell method is carried out after the adjacency matrix which shows the relationship between the subjects is constructed. Class schedules with 8 subject groups (slots) are generated and distributed to each lecture session with a maximum of 5 sessions Monday to Friday. Course schedules with weights of 4 and 3 credits are carried out in 2 sessions each week. The application of the coloring method is done using the C++ program